Pesticide Safety Miniposter: Labels and Material Safety Data Sheets (MSDSs) - Rebecca W. Baldwin; Stephanie K. Larrick Hill; Philip Koehler; P. A. Mitola; J. C. Medley (EDIS)
You have heard the phrase, “the label is the law.” Pest control technicians need to learn the components of a pesticide label and the information they can find on the Material Safety Data Sheet (MSDS). This poster acquaints new pest control technicians with the information they will find on pesticide labels and on MSDSs. The poster has quick response (QR) codes that direct smartphones to short, online videos explaining how to read pesticide labels and MSDSs. Designed by R.W. Baldwin, S.K. Hill, Philip Koehler, P.A. Mitola, and J.C. Medley, and published by the UF Department of Entomology and Nematology, August 2012.